Mengajarkan Rasa Toleransi Beragama Pada Anak Usia Dini Dalam Persepektif Hadis - indah sri anggita; Muhammad Alfatih Suryadilaga (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
In times of development like today, the number of foreign cultures entering Indonesia is a phenomenon that needs to be considered during early childhood development, teachers and parents do not only focus on six aspects of early childhood development, in the explanation of this article will review teaching Children from an early age get used to accepting religious diversity, in accordance with government policies in adhering to religions, namely: Islam, Christianity, Hinduism, Buddhism, and Khong Hu Cu, everyone has the right to choose religious beliefs. The aim is to educate early childhood to establish a sense of kinship between fellow religious communities by implementing a sense of tolerance in associations, friends, society, and among human beings throughout the world wherever they are. The method in this research is to use a type of approach in the form of literature, where this study collects more information and data, such as articles and journals, books, and historical stories related to research problems in this literature study can also read references -references contained therein are the results of previous people's research. In the discussion or the results of describing the education of tolerance in the perspective of the hadith, one of them is Please help and compassion which is explained in HR and surah al-Hujarat verse 13: (12). The conclusion is that it teaches a sense of tolerance between religious communities in early childhood, provides an understanding of the attitude of tolerance towards children's social life